HUBUNGAN JIWA-RAGA DAN KURIKULUM PENDIDIKAN ISLAM MENURUT IBNU SINA - KATNI, KATNI (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2016)
This study discusses the life philosophy of Ibn Sina that the human soul is divided into three namely (1). Soul plants (2). Animal souls (3). The Human souls. The human soul has two power that is practical to do with the power agency and daya teoritis yang hubungannya dengan hal-hal yang abtrak. The theoretical power has four levels namely, material sence, sence al-angle, The actual sense, sense mustafad. Based on the assessment that the four stages of the mind is a stage of human thinking to acquire knowledge. Humans acquire the knowledge necessary to practice and study hard from material sense to the sense mustafad. It can be used as a foundation in providing curriculum materials on human education. My mind and body are intimately connected. The influence of the soul to the body is not enforced, whenever the soul wants to move the soul, then the price will be asked. It provides recommendations for the development of educational curriculum should put the education of the soul footstool headliner. Ibn Sina formulate curriculum development based on the age of the child's developmental level. Age 3-5 years the formation of a physical, mental and moral. Age 6-14 years: includes reading and memorizing the Koran, religion subject, arabic, poetry lesson, and sports, teaching skills, appropriate talent. Age 14 years to the top, subjects given selected according to their talents and interests of children towards a professional or an expert in a particular field. Keywords: relationship of soul and body, Islamic education curriculum